2013
DOI: 10.1016/j.biopsych.2012.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive-Behavioral Therapy on Neural Correlates of Fear Conditioning in Panic Disorder

Abstract: This study demonstrates the link between cerebral correlates of cognitive (IFG) and emotional ("fear network") processing during symptom improvement across time in PD/A. Further research along this line has promising potential to support the development and further optimization of targeted treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
163
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(175 citation statements)
references
References 61 publications
10
163
1
1
Order By: Relevance
“…An fMRI study investigating the effects of CBT on neuronal networks demonstrated the involvement of the inferior frontal gyrus (BA 45) in the pathology of panic disorders, and in the successful psychotherapy of such disorders (Kircher et al. 2013). Thus, we speculate that parts of the language system are involved in the cognitive processing occurring during symptom improvement in patients with panic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…An fMRI study investigating the effects of CBT on neuronal networks demonstrated the involvement of the inferior frontal gyrus (BA 45) in the pathology of panic disorders, and in the successful psychotherapy of such disorders (Kircher et al. 2013). Thus, we speculate that parts of the language system are involved in the cognitive processing occurring during symptom improvement in patients with panic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The task design and analyses has been described in detail elsewhere 51,52 . Briefly, we employed a differential fear conditioning task that consisted of three phases (familiarisation (F); acquisition (A) and extinction (E)), each subdivided into an early and a late phase.…”
Section: Functional Mrimentioning
confidence: 99%
“…In the acquisition phase, the US (white noise) was pseudo-randomly paired with one of the CS's (coloured spheres). MR images were analyzed using Statistical Parametric Mapping (SPM5; www.fil.ion.ucl.ac.uk) implemented in MATLAB 7.1 (Mathworks Inc., Sherborn, MA; see 51 ).…”
Section: Functional Mrimentioning
confidence: 99%
See 2 more Smart Citations